Emotional feedback for mobile devices - Seebode, Julia (Springer International Publishing, 2015)
This book investigates the functional adequacy as well as the effective impression made by feedback messages on mobile devices. It presents an easily adoptable experimental setup to examine context effects on various feedback messages and applies it to auditory, tactile and auditory-tactile feedback messages. This approach provides insights into the relationship between the affective impression and functional applicability of these messages as well as an understanding of the influence of unimodal components on the perception of multimodal feedback messages. The developed paradigm can also be extended to investigate other aspects of context and used to investigate feedback messages in modalities other than those presented. The book uses questionnaires implemented on a Smartphone, which can easily be adapted for field studies to broaden the scope even wider. Finally, the book offers guidelines for the design of system feedback.